Trakai Castle Court Acts of 1660–1661 from the collection of Vilnius University Library. III - Ušinskienė, Viktorija (Slavistica Vilnensis, 2016)
The catalogue was prepared in the framework of the reseach project “Court Books of the Grand Duchy of Lithuania (GDL): digitization and database” realised by Vilnius University Library in 2011–2014 (VUL, Nr. LIT–5–19). The paper deals with the previously unexplored Trakai Castle Court Acts of 1660–1661 (F7–MDGs, 1660–1661) from the VUL collection. It presents Part III of the critical catalogue of the manuscripts written in Polish and Old Byelorussian (Ruthenian) languages, also as short descriptions of them (pp. 467–708). These documents are important for the research of Lithuanian, Polish and Byelorussian history. Information accumulated in them reflects a broad political, social and cultural panorama of the multilingual GDL society. It enables us to consider them as unique reference books that represent changing sociolinguistic situation of the GDL.